«Lo destrozó con una ráfaga»: la desaparición del otro a través de la ficción en Víbora (2009), de Andrzej Sapkowski - Francisco David García Martín; María Fernández Rodríguez (Anuario de Estudios Filológicos)
This article reflects on the harrowing process of dehumanisation and deprivation of individuality that, unfortunately, occurs in all war scenarios, both in reality and in fiction. Likewise, it will briefly point out how, in fantasy narrative, this process is highlighted in a much more evident and enlightening way, and will analyse the power of suggestion that literature exerts on the reader. To reach these goals, the novel The Viper (2009) by Andrzej Sapkowski has been chosen, in which the plot takes place during the Afghan-Soviet War (1978-1992) in a mythologised territory that has become legendary. As other researchers –and our own previous works on the author under study– suggest concerning the depersonalization of the other, specially of the other who comes from Eastern cultures, this article emphasises the inevitable dehumanisation that operates in any process of otherness, especially in war conflicts, and how literature is not necessarily an escapist balm. On the contrary, Sapkowski’s fiction aims to expose the weaknesses of a society that is weak in the face of the suffering of others. In order to achieve this purpose, and like the Polish author, it will be globally analysed how Western points of view condition our perception of the Eastern ‘enemy’, while at the same time these conclusions will be illustrated with passages from the novel.